Upaya Peningkatan Pemahaman Konsep Pos-pos Neraca dan Ketrampilan Menyusun Laporan Keuangan Melalui Penerapan Metode Pemberian Tugas - Moh. Sochih; Rr. Indah Mustikawati; Indarto Waluyo (Jurnal Pendidikan Akuntansi Indonesia, 2006)
This research is aimed to improve the comprehension of real account concept and the presentation of that account in the right way by giving some assignments to the students. This research uses a class action research method which takes 2 cycles. Every cycle includes 4 steps. The steps are planning, implementation, observation and evaluation, and reflection. The result of first step is instructional design which is arranged based on the result of observation, interview and questionnaire. The learning method used by the lecturer is recitation method. The result shows that the implementation of recitation method can improve the comprehension of real account concept and the presentation of that account in the right way by giving assignments to the students. Students say that they are not serious when they do the assignments. But, the lecturers say that the assignments will determine the final score. It makes students do more serious. Students spent their time to read the financial accounting books and study in the study group. It’s better if there are some equipment which help the learning process held more effective and some activities outside class.